Pemberdayaan Kemampuan Berpikir Kritis Siswa Melalui Model Pembelajaran JiRQA pada Pembelajaran Biologi - Florentina Rahayu Esti Wahyuni; Benediktus Ege; Bustami, Yakobus (Program Studi Pendidikan Biologi, FKIP Unpas,, 2023)
Students' critical thinking skills greatly influence the mindset of students in the 5.0 era. This research aims to determine the critical thinking skills on biology material through the JiRQA learning model. This research used a quasi-experimental method. The population is all students of SMP Nusantara and students of SMP Yosep Khatulistiwa Sintang. The samples were students in class VIII A and VIII B at SMP Nusantara and SMP Yosep Khatulistiwa Sintang, totaling 92 students. The instrument for measuring critical thinking skills is in the form was 8 essay questions. Data analysis using descriptive statistical analysis and inferential analysis. The descriptive statistical analysis results showed that there was an increase in the mean pretest and posttest scores for both the experimental class and the control class. The inferential statistical analysis results show that the significance value of critical thinking skills is 0.000 and greater than alpha 0.05 so, it can be concluded that there was a significant influence of implementing learning strategies using JiRQA learning model on students' critical thinking skills in biology material.